Exploring culinary diversity in Yogyakarta and optimizing tourism through foodiverse application technology / Indra Prianoto Budipratama ... [et al.] - Budipratama, Indra Prianoto; Muslikhah, RR Siti (2024)
The Foodieverse application is a digital technology innovation to introduce regional culinary delights which is designed to make it easier for tourists to explore the culinary delights they want and need. The Special Region of Yogyakarta was the first location to implement this innovation because it is one of the regions in Indonesia that has a significant increase in tourists and students every year. Foodiverse is designed with several interesting features that unite several tourist needs in one application and is user friendly so it is very easy to understand across generations.